2019
DOI: 10.51359/2526-7884.2019.240028
|View full text |Cite
|
Sign up to set email alerts
|

Guilt and Pride Emotions and their Influence on the Intention of Purchasing Green Products

Abstract: The aim of this paper was to analyze the influence of feelings of guilt and pride in the intention of buying green products by consumers considered sustainable. Guilt and pride are two constructs that shapes people’s actions to avoid guilt-making behaviors and keep those proud, making it important to assess how these two constructs act when it comes to sustainability-related actions, in this case for green products. For this purpose, a descriptive quantitative research was used, with the survey of data perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
1
3
0
5
Order By: Relevance
“…Further study was conducted by Lima et al (2019) to examine the impact of pride and guilt on green purchasing intention. The findings indicated that guilt is a potent factor that has the potential to encourage green product purchase intention in comparison to pride.…”
Section: Differential Effects Of Pride and Guiltmentioning
confidence: 99%
“…Further study was conducted by Lima et al (2019) to examine the impact of pride and guilt on green purchasing intention. The findings indicated that guilt is a potent factor that has the potential to encourage green product purchase intention in comparison to pride.…”
Section: Differential Effects Of Pride and Guiltmentioning
confidence: 99%
“…Namun, efek ini tidak selalu tersedia. Misalnya, Lima et al (2019) mendokumentasikan tidak ada hubungan antara kebanggaan dan niat membeli. Juga, Rowe et al (2019) menunjukkan bahwa kesalahan yang diingat tidak terkait dengan niat ini.…”
Section: Pendahuluanunclassified
“…Selain itu, dalam penelitiannya, Kabadayı et al (2015) menunjukkan pengaruh positif perasaan bersalah pada produk hijau setelah mensurvei 172 mahasiswa di Turki. Demikian pula, Lima et al (2019) memverifikasi tanda positif setelah meneliti 138 orang Brasil. Dengan menunjukkan informasi dan bukti ini, kami menyatakan hipotesis dua sebagai berikut.…”
Section: Rasa Bersalah Dan Niat Membeli Produk Hijauunclassified
See 1 more Smart Citation
“…De resto, outros fatores também poderão influenciar o consumo ecológico, tais como os sentimentos do consumidor (Lima, Costa & Félix, 2019). Também é preciso salientar que nem sempre as estratégias de Marketing Verde utilizadas pelas empresas conduzem a um sentimento de confiança por parte dos consumidores (Mangini, Amaral, Conejero & Pires, 2020).…”
Section: Revisão Da Literaturaunclassified